Tanggung Jawab Perseroan Terbatas Dihubungkan dengan Good Corporate Governance dalam Rangka Mencegah Penyalahgunaan Kekuasaan Pemegang Saham - Yulfasni, Yulfasni; Arliman S, Laurensius (Pagaruyuang Law Journal, 2019)
All of the principles of Good Corporate Governance can support the realization of Good Corporate Governance in order to prevent the misuse of shareholder power considering that the Piercing the Corporate Veil principle can be used to prevent illegal acts committed by shareholders, commissioners or directors. Shareholders, commissioners or directors are possible to commit acts against the law and utilize existing facilities for their personal interests by manipulating their actions or the misuse of company assets. The research method used in this article is the normative juridical research method. The final goal of applying the Piercing the Corporate Veil principle above is the existence of Good Corporate Governance, namely good corporate governance. Therefore, the follow-up to the adoption of the Piercing the Corporate Veil principle is its implementation in Good Corporate Governance, which is a good and correct management system.